Cavernous hemangioma in the masticatory space - Marina Nahas Dafico Bernardes; Lucas da Silva Braz; Júlia Ramos de Melo; Cárita Lopes Macêdo; Jordanna Ferreira Lousek; Hugo Fernandes de Paula; Hugo Valter Lisboa Ramos; Claudiney Candido Costa (Einstein (São Paulo))
ABSTRACT Hemangiomas are benign congenital vascular tumors that commonly arise in the head and neck regions. Although they present with indolent growth and involution in most cases, they can cause facial deformities. Hemangiomas have three subtypes: capillary, cavernous, and mixed. The cavernous type is most commonly observed on the lateral wall of the nose or the inferior turbinate. This report describes a case of cavernous hemangioma diagnosed in a rare location in the left retromaxillary masticatory space in a 67-year-old woman. Total excision of the lesion was performed with surgical treatment through the Caldwell-Luc access. Anatomopathological and immunohistochemical examinations suggested a malformative vascular lesion with a cavernous hemangioma pattern and without signs of malignancy.